2015
DOI: 10.1016/j.carbon.2015.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic order and superconductivity observed in bundles of double-wall carbon nanotubes

Abstract: The magnetotransport properties were studied in hundreds of micrometer length double-wall carbon nanotubes (DWCNT) bundles. Above 15 K the resistance shows an ohmic behavior and its temperature dependence is well described using the variable-range hopping for one-dimensional system. The magnetoresistance is negative and can be explained using an empirical model based on spin-scattering processes indicating the existence of magnetic order up to room temperature. At temperatures between 2 K and 15 K the resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
7
10
0
Order By: Relevance
“…[29] The present observations are consistent with recent results on double-wall carbon nanotubes tube DWCNT bundles, in which SC at Tc=15 K was deduced. It is assumed that that adsorbed sulfur may induce structural disorder can locally trigger extra carriers (doping effect) into the graphite/graphene walls and to enhance SC [30]. They are also consistent with theoretical approach which claims that structural disorder, topological defects and/or foreign atoms adsorption (S or P), may induce SC in graphite [31].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[29] The present observations are consistent with recent results on double-wall carbon nanotubes tube DWCNT bundles, in which SC at Tc=15 K was deduced. It is assumed that that adsorbed sulfur may induce structural disorder can locally trigger extra carriers (doping effect) into the graphite/graphene walls and to enhance SC [30]. They are also consistent with theoretical approach which claims that structural disorder, topological defects and/or foreign atoms adsorption (S or P), may induce SC in graphite [31].…”
Section: Discussionsupporting
confidence: 80%
“…It should be noted that in addition to a-CS reported here, the magnetic peaks in the ZFC branch as well as the unusual ZFC>FC behavior, was observed in three other unrelated systems: In (i) chiral-based magnetic memory device [26], in (ii) double DWCNT in which the peak is elusive and disappears after the ZFC run, [30] and unexpectedly (iii) in liver taken from a patient with mantle cell lymphoma (Fig 19). The common denominator is that all four samples contain (a) carbon (the major component in the chiral-based magnetic memory device) and (b) a magnetic element such as Fe or Ni.…”
Section: Discussionsupporting
confidence: 53%
“…6(c,d). -The more disordered the graphite structure or the smaller the size or length of the interfaces the lower is the temperature where superconducting-like behavior is observed [41,42]. -Finally, the I −V curves measured at different temperatures [37] are compatible with the behavior expected for Josephson junctions under the influence of thermal activation [43].…”
Section: Contacting the Interface Edges In Tem Lamellaesupporting
confidence: 62%
“…In their calculations, they also predicted superconductivity behavior for the M@M DWNT. It is important to note that superconductivity had been observed in MWNTs (with the number of walls greater than three) [61,62], but only recently was it observed in DWNTs [28,63,64]. Postupna et al [65] performed calculations on S@S DWNTs, demonstrating the possibility for energy transfer mechanisms involving the two semiconducting tubes constituting the DWNT systems, and confirmed that the phenomenon of energy transfer strongly depends on the commensurability of the DWNTs, as well.…”
Section: Double-and Triple-walled Carbon Nanotubesmentioning
confidence: 97%
“…Devices utilizing bundles of MWNTs, including DWNTs and TWNTs, also showed superconductivity behavior at low temperatures [28,[61][62][63][64]. Shi et al [28] measured devices containing bundles of DWNTs and observed clear signatures of supercurrents for temperatures below the average critical temperature of 6.8 K, as shown in Figure 10a, while Barzola-Quiquia et al [63] observed superconductive behavior in their bundled DWNT samples for temperatures below the critical temperature of 15 K. These systems, DWNTs, can be used to manufacture self-organized nano-Schottky junctions wherein one layer exhibits a semiconducting behavior and the other exhibits a metallic behavior [163]. These double-walled systems can also be used to fabricate nano-p-n junction devices wherein one SWNT exhibits a p-type semiconducting behavior and the other SWNT exhibits an n-type behavior [163].…”
Section: Applications Involving Dwnts and Twntsmentioning
confidence: 99%